Competitive Perspective on Drivers of Research and Development - Branislav ZAGORSEK; Stefan SLAVIK; Natalia ZAGORSEKOVA; Richard BEDNAR (Communications of International Proceedings, 2020)
This paper studies the drivers of company spending on research and development from a competition perspective. We study whether there is a mechanism that leads companies to spend on research and development. We proposed a model describing company spending on research and development explained by competitive forces. Our research helps to understand how the competition drivers of company spending on research and development work and may be useful as a framework for companies to assess their situation and help them find better than chance solutions. We describe a model consisting of competitive forces derived from the Porter's Five Forces framework and how these factors significantly impact the company spending on R&D, using multiple linear regression of variables selected from the World Economic Forum database. Our major contribution is that we identified a model of company spending on research and development majorly and significantly described by means of competition, which is addressing a problem of insufficient research of this topic stated in the literature.
Keywords: research and development; innovation; competition; competitive environment; competitive advantage